Detection of F94L mutation of the MSTN gene in four Indonesian local cattle breeds - Anwar, S.; Volkandari, S. D.; Wulandari, A. S.; Putra, W. P. B.; Sophian, E.; Said, S. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The F94L mutation of the MSTN gene (MSTN-F94L) is considered not to cause disrupted the function of the myostatin gene drastically. Interestingly, this mutation has a very significant effect on muscle mass, carcass, or meat yield and meat quality without any associated severe negative problems. This study aimed to confirm the MSTN-F94L mutation in four local cattle breeds in Indonesia. A total of 518 individuals (140 of Bali, 107 of Sumbawa, 168 of Pasundan, and 103 of Holstein-Friesian (H-F) cattle) were used in this study. Genotype identification was performed by PCR-RFLP method. In the present study showed that the wild-type C allele was fixed (1.000) in Bali, Sumbawa, and HF cattle. However, the wild-type C allele and the mutant A allele were found in Pasundan cattle, even though the frequency of the mutant A allele was very low (0.012). Therefore, in conclusion, the mutation of the MSTN-F94L was detected in Pasundan cattle but no in all three cattle breeds. However, the presence of the mutant A allele in Pasundan cattle allegedly derived from Limousin bulls. The further investigation in other local and exotic breeds and its crossing will answer the status of the MSTN-F94L mutation in local cattle breeds in Indonesia.